2017
DOI: 10.1111/jch.13071
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining medication adherence in black patients with hypertension through the lens of the social determinants of health

Abstract: Despite the prominent place of health disparities on the national research agenda over the past 2 decades, 1 marked racial and ethnic disparities in hypertension between blacks and whites still persist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Although clinical evidence of statin-associated adverse effects based on patient age is lacking, the perceived statin-associated adverse effects among the premature ASCVD population may be another factor in statin discontinuation and lower adherence rates. As previously reported, social determinants, such as health literacy and social support, may be associated with medication adherence . Hence, in the present study, the suboptimal adherence observed among patients with premature or extremely premature ASCVD may be attributed in part to socioeconomic factors.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although clinical evidence of statin-associated adverse effects based on patient age is lacking, the perceived statin-associated adverse effects among the premature ASCVD population may be another factor in statin discontinuation and lower adherence rates. As previously reported, social determinants, such as health literacy and social support, may be associated with medication adherence . Hence, in the present study, the suboptimal adherence observed among patients with premature or extremely premature ASCVD may be attributed in part to socioeconomic factors.…”
Section: Discussionsupporting
confidence: 63%
“…As previously reported, social determinants, such as health literacy and social support, may be associated with medication adherence. 48 Hence, in the present study, the suboptimal adherence observed among patients with premature or extremely premature ASCVD may be attributed in part to socioeconomic factors. Statin misinformation or misconceptions because of a greater reliance on social media–based or non–clinician-based resources and a comparative lack of experience in long-term medication management 49 may contribute to lower rates of statin adherence in patients, especially in those with premature ASCVD.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, these consequences may differentially affect certain patient subgroups and thereby affect adherence to treatment plans. [15][16][17]…”
Section: Shared Decision Making As a Potential Way To Improve Health mentioning
confidence: 99%
“…[28][29][30][31][32] Medication adherence is strongly associated with social determinants, and approaches to improve medication adherence include efforts to promote patient activation, text messaging, consumer-directed care, and pharmacist-led engagement, all of which were integral features of our digital hypertension program. 33,34 Disparities in health outcomes are prevalent when Black patients are compared with White patients, including heart disease, diabetes, cancer, maternal mortality, and infant mortality. [35][36][37][38] Hypertension prevalence and control rates mirror these differences.…”
Section: Discussionmentioning
confidence: 99%